Análise do processo corrosivo em dutos de ferro: um estudo de caso na adutora de Pau dos Ferros – RN - Oliveira, Maéce Pessoa de (Universidade Federal Rural do Semi-Árido, 2018)
The corrosive process is characterized by deterioration of the material caused mainly by the interaction of the metallic material with the corrosive medium. The work consisted of an analysis of the corrosive process in the city of Pau dos Ferros-RN, relating this process with the changes in the parameters of the water that reaches the consumption of the population, as well as problems caused by the consumption of this water . This study was carried out by means of a bibliographical research during its entire realization phase in order to obtain a theoretical basis for the present research. Photographic records were also made in the pipeline to record the constituent equipment of the vessel where the corrosion occurred, for the purpose of making the corrosion triangle for each equipment, and thus to determine preventive and protective techniques against this process. Water samples were collected at the dam that supplies the water pipe and at different points in the city, respectively, for later laboratory analysis of these samples in order to verify changes occurred in the water after passing through the pipe. It was verified that the impeller presents numerous forms of corrosion, having as greater predominance the uniform corrosion and, it was also verified that the water presents modifications after passing through the pipe and, like one of the preventive techniques more recommended, is the painting and coating of the material by means of an ink that presents in its composition, a metal more reactive than the material of the object under study.
Analysis of the corrosive process in iron ducts: a case study in the adductor of Pau dos Ferros - RN
Monografia
Keywords: Corrosão; Água; Pau dos Ferros; Corrosion; Water; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA